Carvacrol Attenuates Diabetic Cardiomyopathy by Modulating the PI3K/AKT/GLUT4 Pathway in Diabetic Mice - Hou, Ning; Mai, Yunpei; Qiu, Xiaoxia; Yuan, Wenchang; Li, Yilang; Luo, Chengfeng; Liu, Yun; Zhang, Guiping; Zhao, Ganjiang; Luo, Jian-dong (Frontiers in Pharmacology, 2019)
Background: Diabetic cardiomyopathy (DCM), a common complication of diabetes mellitus, eventually leads to heart failure. Carvacrol is a food additive with diverse bioactivities. We aimed to study the protective effects and mechanisms of carvacrol in DCM. Methods: We used a streptozotocin-induced and db/db mouse model of types 1 and 2 diabetes mellitus (T1DM and T2DM), respectively. Both study groups received daily intraperitoneal injections of carvacrol for 6 weeks. Cardiac remodeling was evaluated by histological analysis. We determined gene expression of cardiac remodeling markers (Nppa and Myh7) by quantitative real-time PCR and cardiac function by echocardiography. Changes of PI3K/AKT signaling were determined with Western blotting. GLUT4 translocation was evaluated by Western blotting and immunofluorescence staining. Results: Compared with control mice, both T1DM and T2DM mice showed cardiac remodeling and left ventricular dysfunction. Carvacrol significantly reduced blood glucose levels and suppressed cardiac remodeling in mice with T1DM and T2DM. At the end of the treatment period, both T1DM and T2DM mice showed lesser cardiac hypertrophy, Nppa and Myh7 mRNA expression, and cardiac fibrosis, compared to mice administered only the vehicle. Moreover, carvacrol significantly restored PI3K/AKT signaling, which was impaired in mice with T1DM and T2DM. Carvacrol increased levels of phosphorylated PI3K, PDK1, AKT, and AS160, and inhibited PTEN phosphorylation in mice with T1DM and T2DM. Carvacrol treatment promoted GLUT4 membrane translocation in mice with T1DM and T2DM. Metformin was used as the positive drug control in T2DM mice, and carvacrol showed comparable effects to that of metformin on cardiac remodeling and modulation of signaling pathways. Conclusion: Carvacrol protected against DCM in mice with T1DM and T2DM by restoring PI3K/AKT signaling-mediated GLUT4 membrane translocation, and is a potential treatment of DCM.